Analisis Efektifitas dan Efisiensi Sistem CORETAX: Mengukur Kepercayaan Publik di Tengah Transisi Sistem Perpajakan 2025 - deaa, Dear Filzah Nurhaeni (Journal Social Politica, 2025)
The Core Tax Administration System (Coretax) is a strategic step in Indonesia's tax system reform implemented in early 2025. This research aims to analyze the effectiveness and efficiency of Coretax system services with a focus on the level of public trust amid the transition period of the tax system. The approach used is qualitative through a literature study, by analyzing policies, digital infrastructure, and public responses from various literature sources and online data. The results showed that although Coretax was developed with a large budget and aimed to simplify tax administration, its implementation was marked by various technical obstacles, such as system access failures, data integration errors, and lack of socialization to users. This has resulted in declining levels of taxpayer satisfaction and trust in the Directorate General of Taxes. This study emphasizes the importance of public trust to ensure the legitimacy and sustainability of the digital taxation system. Without adequate socialization, technical readiness, and responsive support, even a sophisticated platform may not be able to gain public trust.